TRAINING ON BUSINESS LICENSING THROUGH THE OSS APPLICATION AND MSME GOVERNANCE IN JAMBO MESJID VILLAGE, BLANG MANGAT DISTRICT LHOKSEUMAWE CITY - Yusnidar; Muhammad Multazam; Ayu Anora; Raudhatinur; Teuku Afriliansyah (RADJA PUBLIKA, 2026)
This study aims to enhance the understanding and capacity of Micro, Small, and Medium Enterprises (MSMEs) in Jambo Mesjid Village, Blang Mangat District, Lhokseumawe City, regarding business legality and governance through training on the Online Single Submission (OSS) application. Many MSMEs in the region still lack legal recognition due to limited knowledge, complex licensing procedures, and insufficient socialization from the government. The training was carried out through three main stages: initial socialization of the importance of legality and risk-based licensing regulations, introduction and practice of using the OSS application, and workshops on MSME governance including administration, production, digital marketing, and good governance principles. The results showed a significant improvement in participants’ knowledge, as indicated by an increase in OSS-related understanding from 25–30% in the pre-test to 80–85% in the post-test. Most participants successfully registered their businesses and obtained a Business Identification Number (NIB) during the training, marking their first step toward formal legality. Furthermore, participants gained skills in simple financial management, quality control, and digital marketing practices. The training also raised awareness of good governance as a foundation for sustainable MSME growth. These findings highlight the importance of legality and governance in increasing MSME competitiveness, expanding access to financing, and strengthening legal protection.